The precise energy spectra measurement of laser-accelerated MeV/n-class high-Z ions and protons using CR-39 detectors. (15th February 2016) - Kanasaki, M; Jinno, S; Sakaki, H; Kondo, K; Oda, K; Yamauchi, T; Fukuda, Y
Abstract: The diagnosis method, using a combination of a permanent magnet and CR-39 track detectors, has been developed to separately measure the energy spectrum of the laser-accelerated MeV/n-class high-Z ions and that of MeV protons. The main role of magnet is separating between high-Z ions and protons, not for the usual energy spectrometer, while ion energy was precisely determined from careful analysis of the etch pit shapes and the etch pit growth behaviors in the CR-39. The method was applied to laser-driven ion acceleration experiments using CO2 clusters embedded in a background H2 gas. Ion energy spectra with uncertainty Δ E = 0.1 MeV n −1 for protons and carbon/oxygen ions were simultaneously obtained separately. The maximum energies of carbon/oxygen ions and protons were determined as 1.1 ± 0.1 MeV and 1.6 ± 0.1 MeV n −1, respectively. The sharp decrease around 1 MeV n −1 observed in the energy spectrum of carbon/oxygen ions could be due to a trace of the ambipolar hydrodynamic expansion of CO2 clusters. Thanks to the combination of the magnet and the CR-39, the method is robust against electromagnetic pulse (EMP).